Synthesis of Co+2, Ni+2, Cu+2, and Zn+2 complexes of Schiff base 5-methyl-3-((3, 5-dichlorosalicylidene) amino)-pyrazole, spectral, and biological studies. Issue 1 (17th January 2022) - Devi, Priyanka; Singh, Kiran; Dabas, Pooja
Abstract: Synthesis of a new series of metal complexes (Co +2, Ni +2, Cu +2, and Zn +2 ) with novel bioactive Schiff base 5-methyl-3-((3, 5-dichlorosalicylidene) amino)-pyrazole which was prepared by condensing 3-amino-5-methylpyrazole with 3, 5-dicholorosalicylaldehyde in absolute alcohol under refluxing condition have been carried out. The ligand and its metal(II) complexes were characterized by 1 H NMR, IR, mass spectroscopy, UV–vis, fluorescence, ESR, elemental analyses, magnetic moments, and thermogravimetric (TG/DTG) analysis. With the help of different techniques divulged Cu +2 complexes have exhibited square planar geometry and Co +2, Ni +2, and Zn +2 complexes have octahedral geometry. Stability of all the metal complexes has been calculated by spectrophotometric method. All the compounds were studied towards fluorescent, antibacterial and antifungal activity and exhibited significant fluorescence and biological activity as contrasted to Schiff base. Abstract : UF0001